Two species of Polycelis (Platyhelminthes, Tricladida, Planariidae) newly recorded for the Qinling Mountains and the Loess Plateau in China, with a comparative discussion on their karyotypes - Sun, Xin-Xin; Wang, Lei; Li, Ning; Sluys, Ronald; Liu, De-Zeng; Dong, Zi-Mei; Chen, Guang-Wen (Zootaxa, 2024)
The paper details new geographic records of two species of the genus Polycelis Ehrenberg,1831 (Platyhelminthes, Tricladida, Planariidae) for the Qinling Mountains and the Loess Plateau in China and provides redescriptions of these species based on an integrative taxonomic study involving morphology, karyology, and histology. This new information considerably expands our knowledge on these species, for which until now only limited data was available. The species Polycelis asiatica Selinova, 1985 is characterized by the following features: 63–80 eyes; sperm ducts that exhibit an intrabulbar knee-shaped bend towards the ventral surface before opening separately and symmetrically into the antero-dorsal portion of a large seminal vesicle; the latter is ventrally displaced, thus creating a narrow ventral lip on the penis papilla; dorsal wall of the seminal vesicle is provided with several well-developed folds; more or less bulbous penis papilla protrudes from the dorsal wall of the male atrium and is provided with a slender and flexible tip; chromosome complement diploid with 30 metacentric chromosomes, 8 submetacentric chromosomes, and 2 subtelocentric chromosomes. The species Polycelis eudendrocoeloides (Zabusova, 1929) is characterized by: 49–80 eyes; highly reduced and blunt penis, provided with a kind of flagellum that projects into the seminal vesicle; a relatively thick coat of circular and longitudinal muscles around the entire male atrium; generally, a very large intrabulbar seminal vesicle, extending from near the ventral body surface to occupy the major part of both the penis bulb and the dorso-ventral space of the body; diploid chromosome complement consisting of 36 metacentric chromosomes.